2022
DOI: 10.15835/nbha50112538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gibberellin, nano-nutrition with titanium, zinc and iron on yield and some physiological and qualitative traits of white beans

Abstract: Plant nutrition has a vital role in crop production. This study was performed to investigate the effects of different application methods of some nutrients (nano Fe, Zn, and Ti), and gibberellin on yield, some morphophysiological and grain protein of white beans in 2018 as a factorial experiment in a randomized complete block design with four replications. Experimental factors included seed priming (hydropriming, gibberellin priming, titanium nano dioxide, and nano-Zn priming) and micronutrient foliar spraying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The results demonstrated that nano-K 2 SO 4 enhanced shoot dry weight, plant height, number of flowers, number of tillers, root length, root fresh weight, and root dry weight under both salt levels on two alfalfa (Medicago sativa L.) genotypes [70].…”
Section: The Effect Of Nanofertilizer On Crop Yieldmentioning
confidence: 99%
“…The results demonstrated that nano-K 2 SO 4 enhanced shoot dry weight, plant height, number of flowers, number of tillers, root length, root fresh weight, and root dry weight under both salt levels on two alfalfa (Medicago sativa L.) genotypes [70].…”
Section: The Effect Of Nanofertilizer On Crop Yieldmentioning
confidence: 99%
“…The grain yield was increased by 18% by introducing nano-zinc and spraying iron and zinc. Nano zinc primer sprayed with iron + zinc foliar spray increased grain protein by 21% and significantly increased chlorophyll content in leaves [ 112 ]. With the help of additional irrigation and a combination foliar spray of B + Mn + Zn nano chelate, the greatest wheat yield of 2528.33 kg/ha was produced [ 113 ].…”
Section: Effect Of Nanomaterials (Nms) On Nutritional Quality Of Agri...mentioning
confidence: 99%